Enabling safe aqueous lithium ion open batteries by suppressing oxygen reduction reaction - Chen, Long; Cao, Longsheng; Ji, Xiao; Hou, Singyuk; Li, Qin; Chen, Ji; Yang, Chongyin; Eidson, Nico; Wang, Chunsheng (Nature communications, 2020)
Due to the non-flammable nature of water-based electrolytes, aqueous lithium-ion batteries are resistant to catching fire. However, they are not immune to the risk of explosion, since the sealing structure adopted by current batteries limits the dissipation of heat and pressure within the cells. Here, we report a safe aqueous lithium-ion battery with an open configuration using water-in-salt electrolytes and aluminum oxide coated anodes. The design can inhibit the self-discharge by substantially suppressing the oxygen reduction reaction on lithiated anodes and enable good cycle performance over 1000 times. Our study may open a pathway towards safer lithium-ion battery designs. Despite the non-flammable nature of water-based electrolytes, aqueous lithium-ion batteries still carry an explosion risk due to the sealing structure. Here the authors report a safe aqueous battery with an open configuration, utilizing highly concentrated electrolytes and Al 2 O 3 coated anodes.